Differential gene expression in human granulosa cells from recombinant FSH versus human menopausal gonadotropin ovarian stimulation protocols - Bietz Mandi G; Mueller Breanne A; Eyster Kathleen; Brannian John; Hansen Keith (BMC, 2010)
Abstract Background The study was designed to test the hypothesis that granulosa cell (GC) gene expression response differs between recombinant FSH and human menopausal gonadotropin (hMG) stimulation regimens. Methods Females < 35 years-old undergoing IVF for tubal or male factor infertility were prospectively randomized to one of two stimulation protocols, GnRH agonist long protocol plus individualized dosages of (1) recombinant (r)FSH (Gonal-F) or (2) purified human menopausal gonadotropin (hMG; Menopur). Oocytes were retrieved 35 h post-hCG, and GC were collected. Total RNA was extracted from each GC sample, biotinylated cRNA was synthesized, and each sample was run on Human Genome Bioarrays (Applied Microarrays). Unnamed genes and genes with <2-fold difference in expression were excluded. Results After exclusions, 1736 genes exhibited differential expression between groups. Over 400 were categorized as signal transduction genes, ~180 as transcriptional regulators, and ~175 as enzymes/metabolic genes. Expression of selected genes was confirmed by RT-PCR. Differentially expressed genes included A kinase anchor protein 11 (AKAP11), bone morphogenetic protein receptor II (BMPR2), epidermal growth factor (EGF), insulin-like growth factor binding protein (IGFBP)-4, IGFBP-5, and hypoxia-inducible factor (HIF)-1 alpha. Conclusions Results suggest that major differences exist in the mechanism by which pure FSH alone versus FSH/LH regulate gene expression in preovulatory GC that could impact oocyte maturity and developmental competence.